THE ACQUISITION OF FREE MORPHEME BY A TWO-YEAR OLD INDONESIAN CHILD - Eva Nurtyapul Sri Gustina; Anni Holila Pulungan (LINGUISTICA, 2014)
ABSTRACT The aim of this study was to describe types and how of the free morpheme uttered by a two-year-old Indonesian Child. It was a qualitative research design which was observed with a single case study. The instruments used were observation and interview. The researcher observed the subject for two months where conversation in diffrent contexts in daily activities took place. The data collected were the utterances produced by the subject in diffrent context and interview. The data were analyzed by using the theory of language acquisition and free morpheme. The results of this study were: (1) the two types of free morpheme namely lexical and function word were uttered by the subject in his daily activities in diffrent context. (2) the using of  free morpheme occured analysis were:  saying statement,  refusing advise,  saying  dislike, asking gift, refusing comment,  asking question, and the last is avoiding quarrel. The using of  free morpheme based on the speaker’s backgruond analysis was  internded to be used for the interaction in community. Key words: Acquisition, Free Morpheme, Two Year Old Indonesian Child